Deep Integration, Global Firms, and Technology Spillovers - Jinji, Naoto (Advances in Japanese Business and Economics, 2022)
This open access book explores the impact of deep regional economic integration on spillovers of knowledge and technology across countries. Deep integration through signing deep regional trade agreements (DRTAs), which cover various policy areas in addition to tariff reductions, may or may not facilitate technology spillovers among their signatories. To understand the mechanism of the impact of deep integration on technology spillovers, this book starts by analyzing the behavior of global firms. Factors that affect global firms' activities, such as export, foreign direct investment (FDI), offshore outsourcing, are examined. Micro data on Japanese firms are employed for the analysis. Then, the relationships between bilateral trade patterns and technology spillovers and between types of FDI and technology spillovers are investigated in detail. Patent citation data are used to measure technology spillovers. Finally, the impact of DRTAs on international technology spillovers is analyzed. This book is highly recommended to readers who are interested in the effects of deep regional integration, including academic scholars, policymakers, and graduate students.